Upaya Meningkatkan Kualitas Derajat Kesehatan Lingkungan Melalui Perubahan Perilaku Kesehatan - Septiadi, Wiriasto Herry (UI Scholars Hub, 2007)
The change sanitation behaviour is one efford to increase the healthy quality of the environment. The hygiene disposal excreta is one activities to develop quality for healthy environment. Disposal excreta have relatation with human behaviour/habits. The bad sanitation behavior and unsaniter condition from sanitation services could make environment polution. Based on that condition, one efford to enhance the quality of the environment is by changing sanitation behaviour.